PREVENTIVE EFFECT OF SACCHARUM SPONTANEUM LINN.AGAINST GLYCOLIC ACID – INDUCED UROLITHIASIS IN MALE WISTAR ALBINO RATS - M,SATHYA; DR. R.KOKILAVANI (International Journal of Pharma and Bio Sciences, 2013)
The aim of the present study was to evaluate the antilithiatic activity of Saccharum spontaneum Linn. Healthy male Wistar rats were used in the present study and were divided randomly into 5 groups. Group I was served as normal control. Lithiasis was induced in rats by fed with a calculi-producing diet (CPD: commercial diet mixed with 3% glycolic acid) for 28 days (group II). The levels of protein, sodium, potassium, and chloride and lipid peroxidation were altered in urolithiatic rats. Supplementation with ethanolic extract of S.spontaneum (200 and 300 mg / kg body weight) by oral administration for subsequent 28 days at a rate of 1.0 ml / rat / day restored the levels and it brought back the values to near normal range in urolithiatic rats. The results indicate that the ethanolic extract of S.spontaneum is endowed with significant antiurolithiatic activity. Accordingly, it can be concluded that the supplementation of S.spontaneum root has a beneficial effect on urolithiasis induced by glycolic acid.